2004
DOI: 10.1159/000080159
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Second-Trimester Free β-hCG as an Isolated Finding and Pregnancy Outcomes

Abstract: Objective: To investigate the relationship between unexplained elevated second-trimester free β-human chorionic gonadotropin (β-hCG) levels and pregnancy complications as well as adverse pregnancy outcomes. Methods: The study cohort comprised 2,110 non-smoking women with chromosomal and structurally normal fetuses at low-risk for both Down’s syndrome (risk <1:250) and neural tube defects (maternal serum α-fetoprotein <2.0 MoM). A free β-hCG value of ≧2.0 MoM was used to define the populations with elevated lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…However, the correlation of β-hCG and the incidence of pregnancy complications and adverse pregnancy outcomes have been controversial. Some studies suggested that high levels of β-hCG have no significant correlation with the incidence of IUGR, PIH, PD, and GDM [16]. In contrary, other studies concluded that high levels of β-hCG in the second trimester predict a high incidence of complications during pregnancy and poor pregnancy outcomes [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…However, the correlation of β-hCG and the incidence of pregnancy complications and adverse pregnancy outcomes have been controversial. Some studies suggested that high levels of β-hCG have no significant correlation with the incidence of IUGR, PIH, PD, and GDM [16]. In contrary, other studies concluded that high levels of β-hCG in the second trimester predict a high incidence of complications during pregnancy and poor pregnancy outcomes [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…There were 23 primary articles, of which 19 evaluated the use of mid-trimester maternal serum hCG as a predictor of spontaneous preterm birth (n = 177,730 women) 157,158,162,165,166,[184][185][186][187][188][189][190][191][192][193][194][195][196][197] while one article evaluated it in early first trimester (n = 169), 198 and three articles evaluated cervicovaginal hCG as a predictor of spontaneous preterm birth in women who presented with symptoms of threatened preterm labour (n = 248). 139,199,200 Appendix 5, Table 85 summarises each study's salient features, stratified according to the population of women tested, i.e.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…There were nine case-control studies in asymptomatic women 165,185,186,[189][190][191][192][193]195 and one in symptomatic women. 139 Four studies in asymptomatic women reported consecutive enrolments, 157,166,194,197 while none was reported in symptomatic women.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Free beta-hCG is a subunit of hCG a hormone produced by trophoblastic vili during pregnancy [11]. Elevated freebeta-hCG were found in pregnancies with fetuses with Down syndrome and preeclampsia [12].…”
mentioning
confidence: 99%